The Effect of Service Failures and Service Quality on Customer Loyalty and Repurchase Intentions: A Case Study of Lion Air Group During the COVID-19 Pandemic - Dian Octaviani, Reni; Nathaniel Rusdianto, Benedictus; Ajeng Nuralifah, Dhaifina; Warsito Wangun, Tito; Simarmata, Juliater; Novembriani Irenita, Mustikasari (KnE Social Sciences, 2023)
The COVID-19 pandemic restricted people’s movement and forced airlines to cancel or reschedule flights. Lion Air Group is one example, cutting at least 65% of their regular frequency and rescheduling flights since March 2020. This paper aimed to examine the effects of service failure and service quality of Lion Air Group on their passengers’ loyalty and repurchase intention during the COVID-19 pandemic. 100 respondents participated through an online questionnaire, and SEM-PLS was used for quantitative analysis. It was found that the service quality of Lion Air Group influenced passenger loyalty. Following this, passenger loyalty significantly influenced repurchase intention. Interestingly, passengers did not consider service failures as a factor that influenced their decision to be loyal and fly again with Lion Air in the future, but rather the service quality of the airline group when handling service failures. Keywords: service failure, service quality, customer loyalty, repurchase intention, Lion Air, Batik Air, Wings Air, COVID-19, airline